Evaluating the riskiness of initial public offerings: 1980 - 2000 - Stavros Peristiani (Federal Reserve Bank of New York, 2003)
In the wake of the dot.com collapse, investor sentiment toward initial public offerings (IPOs) has turned negative. To many investors, IPOs have come to symbolize the insider abuses and stock market excesses of the Internet bubble period; to others, investing in IPOs is inherently fraught with danger. This paper asks the question, Have IPOs indeed become more perilous to the investing public over time? I employ two approaches to investigate the post-issue riskiness of IPOs for the 1980-2000 period. First, I compare the stock price volatility for issuing and nonissuing firms. Second, I use a qualitative model to estimate the likelihood that new issues will survive in the aftermarket. Both methodologies show that the riskiness of IPO shares relative to the shares of a nonissuing peer group has increased roughly 30 percent in the 1990s. Although the proliferation of Internet companies in this period helps account for the increased risk, my empirical analysis reveals a more gradual shift in risk that cannot be fully explained by the high-tech bubble. Specifically, I find that companies taken public by top-tier underwriters or funded by venture capital exhibit higher relative volatility and a lower likelihood of survival.
Keywords: G3; G24; 330; initial public offerings (IPOs); relative risk of IPOs; probability of delisting; adverse selection; underwriter-issuer agency conflicts; Internet IPOs; Wertpapieremission; Risiko; Volatilität; Aktienmarkt; Going Private; USA